The ink is still wet: A photographic analysis of Lisbon´s streetsigns - Holton-Raphael, Antonia Maya (My University, 2025)
"THE INK IS STILL WET is a photographic and written investigation into Lisbon’s “streetsigns”—an umbrella term encompassing graffiti, posters, stencils, stickers, and other ephemeral urban inscriptions. Developed under the master program in Design and Visual Culture of IADE - Universidade Europeia, this project uses streetsigns as tools for decoding urban identity and storytelling. I argue that these markings, scattered across the city’s surfaces, operate as a visual language through which residents, visitors, and anonymous actors stake claims to space, assert belonging, and engage in dialogue with the city and each other. In this text, I investigate why people leave these signs, their impact on the urban environment, and why photography is a well-positioned tool to examine and preserve them. Drawing from a broader theoretical framework of urban sociology, semiotics, visual culture, and photographic studies, this project positions Lisbon’s streetsigns as meaningful traces of social life, embedded in the urban fabric and responsive to ongoing processes of gentrification, displacement, and global events. Structured around a photobook of the same title, THE INK IS STILL WET uses analog photography as both a method of documentation and a tool for interpretation—an expressive research tool capable of preserving and reframing fleeting visual culture. The resulting images capture not only what is written on the street but how it interacts with place-specific elements such as weather, architecture, and decay. The images shine light on how these ephemeral interventions contribute to place identity, cultural memory, and collective resistance. This text also provides a closer look at the creative process behind the photobook, tracing the arc from fieldwork and image collection to the curatorial decisions of layout, sequencing, and material form. Rather than aiming for a comprehensive catalog of Lisbon’s signage, THE INK IS STILL WET presents an atmospheric and interpretive reading of the city—one that considers not only what is said, but how, where, and why. It invites the viewer to read the street as a site of visual dialogue, where voices are fleeting, contested, and constantly unfolding.
Keywords: Artist book; Photography; Visual semiotics; Urban inscriptions; Image